PARTISIPATORY DIRECTING IN THE FILM NOISE IN SILENCE - Syam, Reskyana; Adji, Titus Soepono; Fauzi, Abas (Capture : Jurnal Seni Media Rekam, 2020)
Deaf people are social groups that are protected by the Law of the Republic of Indonesia Number 8 of 2016 concerning Persons with Disabilities, but they still feel injustice or unfair in the world of education and in society environment. The above problems are the basis for the creation of the documentary film Noise In Silence. The type of research used is artistic research which produces a documentary film work. Documentary film production is carried out using a participatory directing style, while the analysis uses a visual approach. The resulting documentary film shows the participatory style can support the discovery of answers to the director's doubts, and can reveal the subject's experience in depth so that it can be captured by the audience. In addition, the dramatization of the presentation was successfully realized, so that this film has a high influence on the emotional level of the audience.